Los espacios lúdicos en Lima: El caso de Eureka Café - Ayala Koo, Rodrigo Abelardo (2019)
Nowadays, entertainment through digital platforms is the norm. In such an era, the game café business is on the rise. This model utilizes social interactions born while drinking coffee in a coffee shop and playing tabletop games, thus creating a space for social interaction and development of the individuals’ imagination. The model was first brought to Peru in 2016, with the opening of Eureka Café Lúdico. The following paper aims to identify the reasons why a community of players chooses to use Eureka as a space of interaction and socialization. The methodology relies on ethnography, interviews with the owner and some testimonials from the clients.